PENGARUH E-PROMOTION DAN VIDEO CONTENT TERHADAP MINAT BELI PADA TIKTOK SHOP MELALUI COSTUMER TRUST SEBAGAI VARIABEL INTERVENING - Muhammad Alif Qadafi; Fitriani Latief; Mariah Mariah (Jurnal Bisnis dan Kewirausahaan, 2023)
This research uses quantitative methods. Data was collected through questionnaires and processed using SPSS. This study took a sample of 68 students of the Indonesian Nobel Institute of Technology and Business Makassar The results show that (1) E-Promotion has no significant effect on purchase intention (2) Video Content has no significant effect on purchase intention (3) E-Promotion has a significant effect on Customer Trust (4) Video Content has a significant effect on Customer Trust (5) Customer Trust has a significant effect on buying interest (6) E-Promotion has a significant effect on Buying Interest on TikTok Shop through Customer Trust (7) Video Content has a significant effect on Buying Interest on TikTok Shop through Customer Trust